SOCIALIZATION STRATEGY OF DISASTER MITIGATION ABOUT FLASH FLOOD NEWS IN EAST NUSA TENGGARA PROVINCE - Ari Kurnia; Salsabila Fitri; Chania Humayrha; Citra Wulandani (Universitas Nasional, 2022)
Indonesia is one of the countries in the world that is prone to various types of natural disasters such as Volcanic Eruptions, Earthquakes, Tsunamis, Landslides and Floods. The Geographical condition of the Indonesian territory makes it vulnerable to various kinds of natural disasters (BNPB, 2018). For the development of communication science, Mass Media's role is completed by acceleration of information from Online Media then Social Media. Now, industry too fast to self-involved in publishing information through Social Media. Disaster information must be conveyed by the Mass Media and socialization efforts from the disaster are also needed to community can anticipate further disasters. This research has the significance of how BNPB as a disaster management institution is able to utilize verified Social Media to provide information disclosure. Socialization delivered by Mass Media to Social Media has the same goal, as a tool to convey various disaster efforts that are equipped with data and guidelines. One of the Social Media used as an effort to socialize disaster mitigation is Twitter @BNPB_Indonesia which aims to convey information about disaster mitigation facilities in order to reduce the adverse effects caused by disasters that occur. The purpose of this study is to find out how the disaster mitigation strategy of BNPB through Twitter manages information disclosure. This study uses a Qualitative Approach with the Case Study method on the object of research on the official Twitter account of BNPB, through observation of data on information shared on BNPB's Twitter during the Flash Flood disaster in April 2021, which is studied with Media Consumption Theory. The conclusion of this research is Twitter @BNPB_Indonesia has implemented a flash flood Disaster Mitigation Strategy in Nusa Tenggara Timur Province properly and transparently, reinforced by various data and guidelines in the Buku Saku Hadapi Banjir that published by BNPB in 2019.